Distinct Cytokine and Chemokine Profiles in Autism Spectrum Disorders - Han, Yvonne M. Y.; Cheung, Winnie K. Y.; Wong, Chun Kwok; Sze, Sophia L.; Cheng, Timmy W. S.; Yeung, Michael K.; Chan, Agnes S. (Frontiers in Immunology, 2017)
Previous studies have shown that immunological factors are involved in the pathogenesis of autism spectrum disorders (ASD). However, this research has been conducted almost exclusively in Western contexts, and only a handful of studies on immune measures have been conducted in Asian populations, such as Chinese populations. The present study examined whether immunological abnormalities are associated with cognitive deficits and problem behaviors in Chinese children with ASD and whether these children show different immunological profiles. Thirteen typically developing (TD) children and 22 children with ASD, aged 6-17 years, participated voluntarily in the study. Executive functions and short-term memory were measured using neuropsychological tests, and behavioral measures were assessed using parent ratings. The children were also assessed on immunological measures, specifically, the levels of cytokines and chemokines in the blood serum. Children with ASD showed greater deficits in cognitive functions, as well as altered levels of immunological measures, including CCL2, CCL5 and CXCL9 levels, compared to TD children, and the cognitive functions and associated behavioral deficits of children with ASD were significantly associated with different immunological measures. The children were further sub-classified into ASD with only autistic features (ASD-only) or ASD comorbid with attention-deficit hyperactivity disorder (ASD+ADHD). The comorbidity results showed that there were no differences between the two groups of ASD children in any of the cognitive or behavioral measures. However, the results pertaining to immunological measures showed that the children with ASD only and ASD+ADHD exhibited distinct cytokine and chemokine profiles and that abnormal immunologic function was associated with cognitive functions and inattention/hyperactivity symptoms. These results support the notion that altered immune functions may play a role in the selective cognitive and behavioral symptoms of ASD.